Optimization of water blanching and cabinet drying conditions for preservation of nutritional and phytochemical properties of moringa leaves - Neelavathi, R; Rani , C I; Arumuganathan , T (Plant Science Today, 2025)
The perishable nature of moringa leaves leads to its limited shelf life. Drying methods reduce water activity and help extend the shelf life of dried leaves. In this study, the moringa leaves were subjected to water blanching at 50, 60, 70 and 80 oC for 1, 2 and 3 min, followed by drying. Water blanching at 50 °C for 3 min resulted in the highest retention of total carotenoids (24.65 mg/100 g), iron (21.50 mg/100 g), calcium (1413.10 mg/100 g) and colour of dried moringa leaves. To assess their impact on nutrient retention, the water-blanched moringa leaves were then subjected to three different drying methods: cabinet drying, sun drying and shade drying. The drying methods significantly influenced the retention of nutrients, with varying degrees of effectiveness across methods in moringa leaves. The moringa leaves blanched in water at 50oC for 3 min and dried in a cabinet drier retained the higher total carotenoids (24.65 mg/100 g), iron (21.50 mg/100 g) and calcium (1413.10 mg/100 g).